2020
DOI: 10.1111/aor.13808
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical circulatory support for early surgical repair of postinfarction ventricular septal defect with cardiogenic shock

Abstract: Postinfarction ventricular septal defect (pVSD) due to acute myocardial infarction complicated by cardiogenic shock (CS) is associated with high mortality. The aim of this study was to determine the outcome of primary surgical repair of pVSD in patients with CS and examine whether it is influenced by the use of mechanical circulatory support (MCS) devices. Between October 1994 and April 2016, primary surgical repair of pVSD complicated by CS was performed in 53 patients. Thirty‐six (68%) were implanted pre‐ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…This is consistent with what was reported by Vondran et. al 14 . who recently investigated the role of mechanical support in 53 patients with VSD and cardiogenic shock and found that use of preoperative IABP was not of further benefit for patients waiting for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what was reported by Vondran et. al 14 . who recently investigated the role of mechanical support in 53 patients with VSD and cardiogenic shock and found that use of preoperative IABP was not of further benefit for patients waiting for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing the data on 53 patients with post-infarcted ventricular septal defect complicated by cardiogenic shock, Vondran et al found that the time from infarction to surgery was the predictor of mortality in the 30-day observation [ 14 ]. Performing surgery up to 7 days after the infarction is associated with worse results (OR 5.894; p = 0.007); preoperative use of IABP does not reduce mortality rate (of the 36 patients, 16 survived) whereas preoperative use of ECMO tends to improve the early survival rate among patients with post-infarction VSD (used in four patients, three of whom survived).…”
Section: Resultsmentioning
confidence: 99%
“…Several publications do not provide data relevant for this review. Some studies reveal incomplete data concerning duration of mechanical circulatory support without precise distinction on pre- and postoperative use of MCS (Mateucci et al [ 41 ], Huang et al [ 40 ], Ronco et al [ 38 ], Rob et al [ 39 ], Vondran et al [ 14 ]) and, in some cases, the temporal possibilities of postponing the surgery. In addition, some retrospective studies include patients not only with VSR but also with other mechanical complications of myocardial infarction (Mateuci et al [ 41 ], Fujimoto et al [ 42 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time frame, physicians should be able to stabilize the patient's hemodynamics, correct any organ failure, and unload the ventricles in order to promote myocardial recovery before VSD correction. Acute mechanical circulatory support (aMCS) is thus often discussed for this purpose; however, the type and timing of its deployment are still a matter of debate ( 10 ).…”
Section: Introductionmentioning
confidence: 99%